Migration and Remittances Nexus: Economic Implications and Analysis - Wadim Strielkowski; Lenka Šperková; Brożyna Jacek (Amfiteatru Economic Journal, 2017)
The main goal of our paper was to apply our research methodology on the specific case of the Ukrainian migration and remittances in the Czech Republic. In contrast to previous studies, we provide a more detailed insight into the specifications of remittance behaviour and test assumptions in the Ukraine-Czech Republic country models. A range of testing is defined by the hypotheses capturing determinants of probability to send mo ney transfers, their volume, spending behaviour and probability of having skilled position. Our results demonstrate that reverse economic effects of remittances on the source country might be simply combination of regular and occasional form with different weight. Therefore, we conclude that the development of migration policy should not neglect microeconomic effects that have potential to solve aggregate level problems .
Keywords: C31; E27; F24; F22; J15; Y10; 330; migration; remittances; labour market; Ukraine; Poland; United Kingdom; European Union